A computational study of 3D flow structure in two consecutive bends subject to the influence of tributary inflow in the middle Yangtze River. Issue 1 (31st December 2023) - Lu, Guangwei; Liu, Jinxin; Cao, Zhixian; Li, Youwei; Lei, Xueting; Li, Ying
Abstract : Enhanced understanding of turbulent flow structure in bends in natural rivers is essential for waterway regulation, navigation safety and environmental and ecological wellbeing. However, the flow structure in consecutive bends has so far remained poorly understood, especially when it is subject to the influence of tributary inflow. Here, the 3D flow structure in two consecutive bends, namely Qigongling (upstream bend) and Guanyinzhou (downstream bend), subject to the influence of tributary inflow from the Dongting Lake, in the middle Yangtze River, is numerically investigated. The RNG k - ϵ turbulence model is applied under the FLOW-3D software platform. The results show that: (1) the high-velocity zones shift from inner to outer banks in both consecutive bends. (2) No secondary current cells are spotted at the entrance of either bend. At the bend apex, multiple cells of secondary currents appear in Qigongling, but not in Guanyinzhou under certain discharges. (3) Recirculation vortices occur mainly on the inner bank (small-scale) in Qigongling, but on both the inner (small-scale) and outer (large-scale) banks in Guanyinzhou. (4) With increasing mainstem (tributary) discharge, the velocity and turbulent kinetic energy enlarge (reduce). However, a decrease of the secondary current strength in Qigongling and an increase in Guanyinzhou (all increase in both bends).